2022
DOI: 10.3389/fpsyg.2022.805796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daylight Perception Assessment Methods

Abstract: Daylight is an important component in maintaining human health and wellbeing and plays a key role in physiological, psychological, and behavioural regulation. Understanding the complexity of daylight perception is vital since the degree of satisfaction with daylight conditions could greatly impact individual mood, behaviour and cognitive performance. This paper aims at (1) presenting an overview of current knowledge on methods for assessing daylight perception and (2) establishing a methodology for assessing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Although all rooms have been less utilised after COVID-19, Room 2 still has the highest occupancy at 47.5%. Previous research [ 11 , 33 , 34 ] revealed that the reason for the high selection of desks in this room is the accessibility to daylight and outdoor views.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all rooms have been less utilised after COVID-19, Room 2 still has the highest occupancy at 47.5%. Previous research [ 11 , 33 , 34 ] revealed that the reason for the high selection of desks in this room is the accessibility to daylight and outdoor views.…”
Section: Resultsmentioning
confidence: 99%
“…Since collecting data from individuals in the real world was not feasible, this study used motion sensors to track changes in students’ library usage over an extended period of time. The methodology is based on the assumption that occupancy monitoring data accurately represents the individuals’ seating preferences because an experiment in the Bartlett Library [ 33 , 34 ] and a subsequent occupancy monitoring study [ 11 ] both identified specific spaces as being the most occupied and most in-demand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sunlight is important for human health and helps regulate physiology, psychology, and behavior ( 1 ). For example, sunlight influences melatonin secretion, which in turn affects circadian pacing by the supraoptic nucleus in the brain, such that lack of natural daylight can disturb sleep–wake rhythms ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that sunny weather and good daylight could improve mood ( 23 , 27 ), relieve stress ( 28 ), improve perception ( 29 ) and promote physical and mental health ( 30 ). Ulrich ( 31 ) found that daylight can affect people’s environmental preference, thereby affecting restorativeness.…”
Section: Introductionmentioning
confidence: 99%